1, 25-Dihydroxycholecalciferol (calcitriol) modifies uptake and release of 25-hydroxycholecalciferol in skeletal muscle cells in culture. Issue 177 (March 2018) - Abboud, M.; Rybchyn, M.S.; Ning, Y.J.; Brennan-Speranza, T.C.; Girgis, C.M.; Gunton, J.E.; Fraser, D.R.; Mason, R.S.
Highlights: Skeletal muscle cells accumulate tritiated 25(OH)D in a time dependent manner. Three hour pre-incubation with calcitriol increased net uptake of trititated 25(OH)D and intracellular DBP concentrations. Sixteen hour pre-incubation with calcitriol reduced net uptake of trititated 25(OH)D, with unchanged intracellular DBP concentrations. The effects of calcitriol pre-incubation were abolished by DIDS and in muscle fibers from VDR knockout mice. Calcitriol modulates net uptake and retention of 25(OH)D by skeletal muscle. Abstract: The major circulating metabolite of vitamin D3, 25-hydroxycholecalciferol [25(OH)D], has a remarkably long half-life in blood for a (seco)steroid. Data from our studies and others are consistent with the hypothesis that there is a role for skeletal muscle in the maintenance of vitamin D status. Muscle cells internalise vitamin D-binding protein (DBP) from the circulation by means of a megalin/cubilin plasma membrane transport mechanism. The internalised DBP molecules then bind to actin and thus provide an intracellular array of high affinity binding sites for its specific ligand, 25(OH)D. There is evidence that the residence time for DBP in muscle cells is short and that it undergoes proteolytic degradation, releasing bound 25(OH)D. The processes of internalisation of DBP and its intracellular residence time, bound to actin, appear to be regulated. To explore whether 1, 25-dihydroxycholecalciferol (calcitriol) has any effect on this process, cell cultures of myotubes and primary skeletal muscle fibers were incubated in a medium containing 10 −10 M calcitriol but with no added DBP. After 3 h pre-incubation with calcitriol, the net uptake of 25(OH)D by these calcitriol-treated cells over a further 4 h was significantly greater than that in vehicle-treated control cells. This was accompanied by a significant increase in intracellular DBP protein. However, after 16 h of pre-incubation with calcitriol, the muscle cells showed a significantly depressed ability to accumulate 25(OH)D compared to control cells over a further 4 or 16 hours. These effects of pre-incubation with calcitriol were abolished in fibers from VDR-knockout mice. The effect was also abolished by the addition of 4, 4' -diisothiocyano-2, 2' -stilbenedisulfonic acid (DIDS), which inhibits chloride channel opening. Incubation of C2 myotubes with calcitriol also significantly reduced retention of previously accumulated 25(OH)D after 4 or 8 h. It is concluded from these in vitro studies that calcitriol can modify the DBP-dependent uptake and release of 25(OH)D by skeletal muscle cells in a manner that suggests some inducible change in the function of these cells.